An effective rate approach to modeling single‐stage spray drying. Issue 12 (18th July 2015) - George, Oluwafemi Ayodele; Chen, Xiao Dong; Xiao, Jie; Woo, Mengwai; Che, Liming
Abstract : An effective rate approach (ERA) is proposed to achieve a fast and reliable prediction of dryer outlet conditions for a given single‐stage spray drying system operated under a range of scenarios. This approach is improved from existing methods based on simple mass and energy balances due to the incorporation of a reliable drying rate model, which is the reaction engineering approach for the material of interest. It allows quick solution procedure without the need to solve the partial differential equations that govern the heat and mass transfer in the spray drying process. By following a generic procedure, this technique has been exercised on the experimental results from running a monodisperse droplet spray dryer, that is, a well‐established experimental platform for model validation. The proposed ERA has been shown to be rather promising. It could become a powerful approach for proactive control and optimization for existing spray drying facilities. © 2015 American Institute of Chemical Engineers AIChE J, 61: 4140–4151, 2015